Building evidence and measuring clinical outcomes for genomic medicine. Issue 10198 (17th August 2019) - Peterson, Josh F; Roden, Dan M; Orlando, Lori A; Ramirez, Andrea H; Mensah, George A; Williams, Marc S
Summary: Human genomic sequencing has potential diagnostic, prognostic, and therapeutic value across a wide breadth of clinical disciplines. One barrier to widespread adoption is the paucity of evidence for improved outcomes in patients who do not already have an indication for more focused testing. In this Series paper, we review clinical outcome studies in genomic medicine and discuss the important features and key challenges to building evidence for next generation sequencing in the context of routine patient care.